EFFECT OF GAMMA IRRADIATION ON GROWTH OF ESCHERICHIA COLI AND SALMONELLA SP. - Dita Aisyiyah Larasati; Bambang Suharto; Ruslan Wirosoedarmo; Irawan Sugoro (HIMNI, 2021)
Escherichia coli was still detected in treated water and Salmonella sp. filled 90% of the pathogenic bacteria content in the Wastewater Treatment Plant (WWTP) sludge. This research aimed to know the effect of gamma irradiation on the growth of E. coli and Salmonella sp. Experimental bacteria were in the form of un-raw material, bacterial isolates. The experimental method of this research gave gamma irradiation doses 1, 2, 3, 4, and 5 kiloGray (kGy) to bacterial suspensions. The isolates were cultured on Nutrient Agar (NA) and followed by cultured on Nutrient Broth (NB) to get the suspensions. The suspensions were put in microtubes for irradiation then followed by enumeration on Plate Count Agar (PCA) in Total Plate Count (TPC) based on SNI-2897-2008. This research proved that the higher dose of gamma irradiation had been given, the lower growth of bacteria (or were the higher death number of bacteria) resulted. Decimal Reduction Dose (D10) value of E. coli and Salmonella sp. were 0,3 kGy and 0,35 kGy, and totally dead by â‰¥ 3 kGy and â‰¥ 4 kGy. For further research might be conducted on raw material such as WWTP sludge, wastewater, drinking water, river water, soil water, or organic fertilizer.EFFECT OF GAMMA IRRADIATION ON GROWTH OF ESCHERICHIA COLI AND SALMONELLA SP.